2020
DOI: 10.1002/adfm.202001118
|View full text |Cite
|
Sign up to set email alerts
|

Gradiently Sodiated Alucone as an Interfacial Stabilizing Strategy for Solid‐State Na Metal Batteries

Abstract: All-solid-state metal batteries (ASSMBs) are attracting much attention due to their cost effectiveness, enhanced safety, room-temperature performance and high theoretical specific capacity. However, the alkali metal anodes (such as Li and Na) are active enough to react with most solid-state electrolytes (SSEs), leading to detrimental reactions at the metal-SSE interface. In this work, a molecular layer deposition (MLD) alucone film is employed to stabilize the active Na anode/electrolyte interface in the ASSMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 44 publications
3
68
0
Order By: Relevance
“…This passivation layer could protect the Na metal from dendritic growth, thus enabling cycling for over 200 h. The molecular layer deposition (MLD) technique has been used to construct an alucone film on Na foil. [ 182 ] As shown in Figure 17d, the (Na@alucone)/SEs/(Na@alucone) symmetric cells could cycle for over 500 h. The enhancement mechanism of alucone originates from the synergistic effect between the insulating unsodiated alucone and the dendrite‐suppressed sodiated alucone, which was demonstrated by high‐resolution X‐ray photoelectron spectroscopy (XPS) spectra of symmetric cell after cycling.…”
Section: Sodium Metal Anode and Interface Engineeringmentioning
confidence: 92%
“…This passivation layer could protect the Na metal from dendritic growth, thus enabling cycling for over 200 h. The molecular layer deposition (MLD) technique has been used to construct an alucone film on Na foil. [ 182 ] As shown in Figure 17d, the (Na@alucone)/SEs/(Na@alucone) symmetric cells could cycle for over 500 h. The enhancement mechanism of alucone originates from the synergistic effect between the insulating unsodiated alucone and the dendrite‐suppressed sodiated alucone, which was demonstrated by high‐resolution X‐ray photoelectron spectroscopy (XPS) spectra of symmetric cell after cycling.…”
Section: Sodium Metal Anode and Interface Engineeringmentioning
confidence: 92%
“…Notably, a direct strategy of a uniaxial compression loaded on a Na/NASICON assembly was proposed to tackle the interfacial crux. [166] The authors demonstrated that an interstitial layer was formed by pressing the Na metal on the NASICON surface, whereby Chemical pretreatments NaBr 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 250 cycles 2017 [48] Bi 1 m NaCF 3 SO 3 in diglyme 0.5 mA cm −2 ; 1 mA h cm −2 1000 h 2019 [139] NaI 1 m NaCF 3 SO 3 in diglyme 0.25 mA cm −2 ; 0.75 mA h cm −2 500 h 2019 [140] PhS 2 Na 2 -rich layer 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 800 h 2020 [141] Na 3 PS 4 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 270 h 2019 [142] Thin film depositions PEALD-Al 2 O 3 1 m NaClO 4 in EC/DEC 0.25 mA cm −2 ; 1 mA h cm −2 400 h 2017 [144] ALD-Al 2 O 3 1 m NaSO 3 CF 3 in diglyme 3 mA cm −2 ; 1 mA h cm −2 500 h 2017 [61] MLD-alucone Na 3 PS 4 solid-state electrolyte 0.1 mA cm −2 ; 0.1 mA h cm −2 475 h 2020 [145] Free-standing protective films Graphene 1 m NaPF 6 in EC/DEC 2 mA cm −2 ; 3 mA h cm −2 300 h 2017 [146] Carbon paper 1 m NaCF 3 SO 3 in diglyme 5 mA cm −2 ; 1 mA h cm −2 1200 cycles 2018 [147] Others Nano-SiO 2 1 m NaPF 6 in diglyme 1 mA cm −2 ; 1 mA h cm −2 800 h 2019 [148] Ionic membrane 1 m NaClO 4 in EC/PC 0.1 mA cm −2 ; -250 h 2017 [149] Polished Na anode 1 m NaOTf in diglyme 5 mA cm −2 ; 2 mA h cm −2 550 h 2018 [150] Inorganic-organic hybrid protective layer 1 m NaPF 6 in diglyme 2 mA cm −2 ; 1 mA h cm −2 500 h 2019 [152] www.afm-journal.de www.advancedsciencenews.com…”
Section: Inorganic Solid Electrolytesmentioning
confidence: 99%
“…(d–f) Reproduced with permission. [ 145 ] Copyright 2020, Wiley. g) Schematic of the fabrication process of free‐standing graphene film on Na metal and its function on Na plating.…”
Section: Stabilization Of the Sei On Na Metal Anodesmentioning
confidence: 99%
“…[95] A molecular layer deposition (MLD) alucone film is employed to stabilize the active Na anode/ sulfide electrolyte interface, which reduced the decomposition of the Na 3 PS 4 electrolyte with narrow electrochemical stability. [97] Theoretical investigations reveal that introducing buffer materials such as HfO 2 , Sc 2 O 3 , and ZrO 2 between sulfide SSE and Na metal can alleviate the interface issues. [98] NaÀ Sn alloys instead of Na metals were used in SSBs to avoid dendrites.…”
Section: Advances In Sciences and Technology To Meet Challengesmentioning
confidence: 99%
“…Meanwhile, sulfide electrolytes have been widely employed and studied due to their better interfacial flexibility, higher room‐temperature ionic conductivity, better physical contact between electrolyte and electrodes than oxide electrolytes that suffer from high grain boundary resistance and rigid instinct [95] . A molecular layer deposition (MLD) alucone film is employed to stabilize the active Na anode/ sulfide electrolyte interface, which reduced the decomposition of the Na 3 PS 4 electrolyte with narrow electrochemical stability [97] . Theoretical investigations reveal that introducing buffer materials such as HfO 2 , Sc 2 O 3 , and ZrO 2 between sulfide SSE and Na metal can alleviate the interface issues [98] .…”
Section: Benefits and Challenges For Na+ Solid Electrolytesmentioning
confidence: 99%